Sleep Disturbances After General Anesthesia: Current Perspectives - Luo, Man; Song, Bijia; Zhu, Junchao (Frontiers in Neurology, 2020)
Abstract: The purpose of this article is to review 1) sleep mechanism under general anesthesia, harmful effects of postoperative sleep disturbances;2) risk factors associated with postoperative sleep disturbances;3) measures to prevent and improve postoperative sleep disturbances. General anesthesia changes the postoperative sleep structure especially in elderly patients after major surgery and results in a high incidence rate of sleep disturbances. Sleep disturbances produce harmful effects on postoperative patients and lead to a higher risk of delirium, more cardiovascular events, and poorer recovery. Some researchers do propose non-pharmacological treatments such as attention to environmental and psychological factors; application of electroacupuncture (EA) technology and pharmacological treatments are helpful, but larger high-quality clinical trials with longer following-up are needed to further investigate the efficacy and safety.